2015
DOI: 10.1177/1932296815617969
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetic Retinopathy Screening Workflow

Abstract: Complications of diabetes mellitus, namely diabetic retinopathy and diabetic maculopathy, are the leading cause of blindness in working aged people. Sufferers can avoid blindness if identified early via retinal imaging. Systematic screening of the diabetic population has been shown to greatly reduce the prevalence and incidence of blindness within the population. Many national screening programs have digital fundus photography as their basis. In the past 5 years several techniques and adapters have been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…To date, much advancement has been made by the manufacturers of smartphones, and thus, proper selection of the available smartphone technology promises a comparable performance between smartphone‐based and conventional techniques. Bolster et al reviewed the diabetic retinopathy (DR) screening methods based on a smartphone and concluded that although pilot studies and single‐site trials have yielded hopeful results for the validation of smartphone‐based DR assessment in comparison with reference standards, more efforts should be made to further develop the smartphone‐based approach. Giardini et al designed a smartphone ophthalmoscope that was integrated on a Galaxy S3 smartphone and employed Java programming to create software that enables video capture, magnification, and segmentation and enables creating measurements.…”
Section: Resultsmentioning
confidence: 99%
“…To date, much advancement has been made by the manufacturers of smartphones, and thus, proper selection of the available smartphone technology promises a comparable performance between smartphone‐based and conventional techniques. Bolster et al reviewed the diabetic retinopathy (DR) screening methods based on a smartphone and concluded that although pilot studies and single‐site trials have yielded hopeful results for the validation of smartphone‐based DR assessment in comparison with reference standards, more efforts should be made to further develop the smartphone‐based approach. Giardini et al designed a smartphone ophthalmoscope that was integrated on a Galaxy S3 smartphone and employed Java programming to create software that enables video capture, magnification, and segmentation and enables creating measurements.…”
Section: Resultsmentioning
confidence: 99%
“…There is particularly great interest in the validation and integration of smartphone-based retinal photography in local community screening programs for diseases such as glaucoma and diabetic retinopathy (DR) [13][14][15][16] , as well as in the emergency department and inpatient settings where the fundus examination is under-performed [17][18][19] . DR is the most common microvascular complication of diabetes and the leading cause of vision loss in working-age adults aged 20 to 74 in the United States, accounting for 12% of new cases annually [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, retinal imaging in primary care offices has been quite successful in eradicating some of the obstacles that impede diabetic patients from undergoing diabetic retinopathy screening [113,122,123,125,126]. Patients with diabetic retinopathy (or ungradeable disease) noted on photographs may be referred to ophthalmologists for further evaluation and treatment; this may eventually lower the number of overall screening referrals to ophthalmology for disease not warranting treatment, thus allowing more resources for evaluation of patients with ungradeable pathology on photos or treatment of those with clearly noted disease [124].…”
Section: Introductionmentioning
confidence: 99%